THE CONTRIBUTION OF BANK IMAGES IN ENHANCING CUSTOMER LOYALTY AT PT BANK MAYAPADA PEMATANGSIANTAR. - Sinaga, Onita Sari; Candra, Vivi; Leony, Leony (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2024)
The purpose of the study is to determine the influence of bank image on customer loyalty. The approach used in the research design is a quantitative descriptive approach. This study uses tests of validity, reliability, normality, simple linear regression, correlation and determination. The results of the study stated that the bank's image had a positive and significant effect on customer loyalty, loyalty at PT Bank Mayapada Pematangsiantar and the level of strong relationships. The bank's image contribution to customer loyalty is 56.2%.